Época e densidade de plantio sobre a fenologia e o rendimento da cúrcuma (Curcuma longa L.) - Cecílio Filho, Arthur Bernardes (1996)
Afield experiment was conducted over the period of october, 1994 to july, 1995 at the Universidade Federal de Lavras, in Lavras (MG), with a view to knowing the response of turmeric to different times and densities of planting in order to establish the best combination for maximization of both the quality and yield of rhyzomes.. The experimental design used was randomized blocks, in split plot, with three replications. The factors evaluated were: planting date 20th/Oct., 20th/Nov., 20th/Nov., 20th/Jan.) and plant spacing on the planting line (20, 35 and 50 cm) amounting to 12 treatments. Significant effect of the factor planting date over the crop cycle was observed, being of 270, 240, 210 and 180 days, respectively, for the plantings of 20th/Oct., 20th/Nov., 20th/Dec, 20th/January. In the same way, the growth stages both vegetative and rhyzomes, were influenced. It was also observed that it was in tillering stage which occurred the greatest increase in absolute value in the dry matter of the aerial part, being considered a key period for the success of the crop. In the characteristics, dry matter of the aerial part (DMAP) and of tillers (DMT) and total leaf area (TLA) there was a significant interation of the factors under evaluation. The planting on 20th/Nov significantly overcame the other planting dates in the expression of the traits quoted. With delayed planting, lower values were found. As regards as the accumulations of nutrients, there was a significant interaction of the factors assessed. Rhyzome production per plant showed with a great deal of resemblance the growth characteristics and nutrient accumulation, reaching 673,13 grams per plant, in the 20th/Nov planting and 36,6 cm spacing. However, the maximum rhyzome yield per area (24.678,84 kg/ha) was obtained in the 20m/Nov planting itself but in the 30 cm plant spacing, spacing which provided also the greatest leaf area index (2.3). Curcumin content was significantly influenced by the factor planting time, a linear reduction of the content of the dye being verified as the planting was delayed. A linear reduction of the yield of the dye was also found for the following plantings: 20th/Oct, 20th/Dec, 20th/Jan as larger spacings were employed. Nevertheless, for the 20th/Nov planting, the yield was maximized when of the use of 30 cm between plants, as well as found for rhyzome yield per area. Extraction of N, P, K, Ca, Mg, S, Be Zn for the maximum yield of rhyzomes and curcumin was, respectively, of 111,83, 21,04, 95,08, 37,03, 24,78, 3,06, 0,04 and 0,42 kg/ha, and nutrient export by turmeric were 109,66, 18,94, 84,28, 13,02, 17,87 2,92, 0,02 and 0,328 kg/ha.